Admission control with batch arrivals - Örmeci, EL; Burnetas, A (Operations Research Letters, 2004)
We consider the problem of dynamic admission control in a multi-class Markovian loss system receiving random batches, where each admitted class-i job demands an exponential service with rate μ, and brings a reward r i. We show that the optimal admission policy is a sequential threshold policy with monotone thresholds. © 2004 Elsevier B.V. All rights reserved.
Keywords: Computer networks; Customer satisfaction; Dynamic admission control; Job analysis; Loss systems; Markov processes; Monotonicity properties; Parallel processing systems; Poisson distribution; Random number generation; Servers; Stochastic control systems; Threshold policies